Manajemen Pembiayaan Pendidikan dalam Meningkatkan Mutu Sekolah SD Negeri Klepu 03 Pringapus Kabupaten Semarang - Abdul Mufid; Noor Miyono; Sumarno (Universitas Muhammadiyah Bangka Belitung, 2025)
The cost of education in Indonesia is relatively high nationally, but the quality of education is still low. The use of education costs does not achieve its goals if its management is not in accordance with the rules. This study aims to describe the planning, implementation, and evaluation of financing in improving quality at Klepu 03 Elementary School, Pringapus, Semarang Regency. The research method uses qualitative descriptive with a case study type. The research subjects include the principal, financial management team, teachers, and school committee. Data were collected through interviews, documentation, and observation, and analyzed qualitatively including data collection, reduction, display, and drawing conclusions. The results of the study show: (1) Financing planning includes cost allocation for the development of educators, learning, facilities and infrastructure, culture, and school environment, as well as school management, with the principles of transparency, accountability, effectiveness, and efficiency. (2) Implementation of financing according to standards involves allocation for improving teacher competence, facilities, culture, environment, and teaching programs. (3) Financing evaluation is carried out through internal auditing by the principal and committee, and externally by government agencies such as the BPK and the Directorate General. These results indicate that financing management at SDN Klepu 03 supports systematic improvement of school quality according to applicable standards.